SUCH A GLOBAL EUROPE - P. P. Aleksandrov-Derkachenko (Vestnik MGIMO-Universiteta)
A review of the publication describing the position of the European Union in the global dimension, as the foreign policy component policy of the European Union, the EU’s relations with different regions of the world. The illustrative book shows the dynamics of the EU’s relations both with individual countries and with major international organizations. The author of the review considers the phenomenon of European integration, in which the boundaries of the territory of the European Union, the Euro zone and the territory of the countriesparticipants of NATO do not coincide and the impact of this phenomenon on the formation of EU foreign policy. Also considers the prospects for the development of the EU’s relations with countries and international organizations, as well as the factor of “catching up development” of the foreign policy development of the EU in comparison with foreign trade.